Libgram assist - Jasmin, Ilani Nur Adriani; Idris, Zaila; Norshahimi, Airul Shazwan; Muzahar, Nur Ain Syakira (Universiti Teknologi MARA, Kedah, 2019)
Many believe that library is still a boring place to visit, as library hold the concept of silence and also very orthodox. The communication that goes on between the staffs and users are restraint only between face-to-face. Librarian faces challenge in redefine the concept of library. In order to attract more users to visit it. LibGram Assist is an arithmetical hologram projection of a librarian in a library environment. Using the latest technology of fairylight, LibGram Assist concept will support the new digital library environment and will forever change the perception of the society about library and information archive. LibGram Assist uses fairy light technology that applies femtosecond lasers to ionize air molecules and thus create crackling, photon-emitting pockets of plasma. These lights, or “voxels,” can be arranged in mid-air to create moving and floating images. The most amazing thing is that these lights are interactive. Not only that you can touch them; you can also feel and control them. Envision, a librarian hologram that looks so real that 3D objects appear to float in mid-air – now this is LibGram Assist. LibGram Assist will help a library to manage librarian routines communication tasks when dealing with users, LibGram Assist is the beginning of a new era where it introduces the surrounding without any help from a human, as it is conducted by the hologram itself. For instance, the LibGram Assist can be used by users to ask and also to get basic information about the library (advance version). LibGram Assist will also help users (including handicapped users) by providing them the direction to find library material and resources. But most importantly, LibGram support both, 4IR and Malaysia TVET vision.